IRAN DI TENGAH HEGEMONI BARAT (Studi Politik Luar Negeri Iran Pasca Revolusi 1979) - Kiki Mikail (Fakultas Adab dan Humaniora UIN Raden Fatah, 2013)
Abstract:This Paper to explain the foreign affairs policies that taken by Iranian Goverment from the begining of Islamic revolution in Iran through the presidency of Hassan rouhani period. Goals of Islamic government of Iran had been fluctuated between interests of Islamic world and interests of Iran; or in other word, between interests of Islam Umma (the nation of Islam) and national interests of Iran. Islamic principles have dominated on foreign policy of Iran but different conditions made the government to change its priorities of Foreign policy. in other word, Iran's foreign policy is always different according to the presiden although still based on revolution values.